Development and Evolution of Palmette Ornament: An Influence on Islamic Architecture - Zahra, Fatima; Shahir, Safrizal (Landscape Architecture and Art, 2022)
Decorative architectural ornaments are the mainstay of several art forms. Islamic architecture had several properties and characteristics, including the non-depiction of living beings and emulating God's creation of wrongdoing. Therefore, floral, geometrical, and vegetal motifs became the main component of Islamic architectural ornaments. Similarly, Palmette is included and practiced on a large scale in Islamic architecture due to its vegetal or floral forms. This article focuses on the historical aspects of palmette ornament. Additionally, it explores the development and evolution of the ornament from west to east. Moreover, how palmette ornaments are practiced in Islamic Architecture. For this purpose, historical approach of description is used to explore and analyze the palmette ornament in depth.